Composite cathode, method for preparing the same, and lithium ion battery
Patent Information
- Application Number
- CN202311795931.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-25
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-12-25
AI Technical Summary
然而添加剂需与电解液的溶液适配,存在添加剂溶解度差的问题,并且电解液中添加剂的数量有限,无法准确控制添加剂在正极侧或负极侧进行反应,优先在负极形成SEI膜就会影响在正极形成CEI膜,影响到正极的循环性能
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, and in particular to a composite cathode and its preparation method, and a lithium-ion battery. Background Technology
[0002] Based on current environmental protection requirements, new energy vehicles using power batteries as a power source are developing rapidly. Using ternary materials or manganese-rich materials as positive electrodes is the current mainstream technology. However, transition metal ions such as manganese ions in ternary materials or manganese-rich materials are prone to detachment, causing transition metals to deposit on the electrode, consuming active lithium ions, resulting in a decrease in battery capacity and deterioration of cycle performance.
[0003] In related technologies, additives are often added to the electrolyte. During formation, these additives decompose to form a CEI (Chemical Electrolyte Injection) or SEI (Sediment Electrolyte Injection) film. These films prevent contact between the electrolyte and the electrode and reduce the dissolution of transition metals. However, the additives need to be compatible with the electrolyte solution, leading to poor solubility. Furthermore, the amount of additive in the electrolyte is limited, making it impossible to accurately control whether the additive reacts on the positive or negative electrode side. Preferential formation of an SEI film at the negative electrode will affect the formation of a CEI film at the positive electrode, thus impacting the cycle performance of the positive electrode. Summary of the Invention
[0004] Based on this, and in response to the above problems, this application provides a composite cathode and its preparation method, as well as a lithium-ion battery, to improve the cycle performance of the cathode.
[0005] The first aspect of this application provides a composite cathode, comprising: a cathode material layer; and a protective layer disposed on the surface of the cathode material layer, the protective layer comprising an additive capable of forming a CEI film on the surface of the cathode material layer under predetermined formation conditions; wherein the additive is a lithium salt.
[0006] The aforementioned composite cathode provides dual protection for the cathode material layer by setting a protective layer on the surface of the cathode material layer and forming a CEI film on the surface of the cathode material layer under preset formation conditions through additives in the protective layer. The protective layer and the CEI film provide dual protection for the cathode material layer, preventing contact between the electrolyte and the cathode material layer, reducing the solubility of the transition metal, and eliminating the need to consider the solubility between the electrolyte and the additives. This effectively improves the cycle performance of the composite cathode and thus improves the cycle performance of the battery.
[0007] In one embodiment, the preset formation conditions include a formation voltage U satisfying U≥4.2V.
[0008] In one embodiment, the lithium salt includes one or more of lithium difluorooxalate phosphate, lithium carbonate, lithium fluoride, lithium difluorooxalate borate, lithium perchlorate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(oxalate borate), lithium bis(oxalate borate), lithium bis(fluorosulfonyl)imide, lithium hexafluoroarsenate, lithium difluorophosphate, lithium difluorodioxalate phosphate, lithium (fluorosulfonyl)(perfluorobutylsulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide, lithium bis(fluoromalonic acid)borate, lithium bis(2-methyl-2-fluoromalonic acid)borate, and lithium 4,5-dicyano-2-trifluoromethyl-imidazolium.
[0009] In one embodiment, the additive has a mass fraction of 1%-45% in the protective layer.
[0010] In one embodiment, the thickness of the protective layer is 0.1 μm-25 μm.
[0011] In one embodiment, the protective layer further includes a solid electrolyte and a binder, which are capable of forming a framework for the decomposition of additives and providing a location for the formation of the CEI membrane.
[0012] In one embodiment, the solid electrolyte includes at least one of an oxide solid electrolyte and a polymer solid electrolyte.
[0013] In one embodiment, the positive electrode material layer includes an active material, which includes at least one of nickel, manganese, and cobalt.
[0014] The second aspect of this application provides a method for preparing a composite cathode as described above, characterized by comprising the following steps: mixing an additive and a solvent to form a protective layer precursor; coating the protective layer precursor onto the surface of a cathode material layer to form a first intermediate product; baking the first intermediate product to obtain a second intermediate product; and pressing the second intermediate product to obtain a composite cathode.
[0015] A third aspect of this application provides a lithium-ion battery, which includes a composite positive electrode, a negative electrode, and a separator as described above. Detailed Implementation
[0016] A detailed reference is now provided to embodiments of this application, one or more of which are described below. Each embodiment is provided for explanation and not for limitation. In fact, it will be apparent to those skilled in the art that various modifications and variations can be made to this application without departing from its scope or spirit. For example, features described or illustrated as part of one embodiment may be used in another embodiment to produce further embodiments.
[0017] Therefore, this application is intended to cover such modifications and variations falling within the scope of the appended claims and their equivalents. Other objects, features, and aspects of this application are disclosed in or will be apparent from the following detailed description. It will be understood by those skilled in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of this application.
[0018] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.
[0019] In this application, numerical ranges are referred to as continuous unless otherwise specified, and include the minimum and maximum values of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.
[0020] In this article, when referring to units for data ranges, if the unit is only followed by the right endpoint, it means that the units for the left and right endpoints are the same. For example, 100~150 nm means that the units for the left endpoint "100" and the right endpoint "150" are both nm (nanometers).
[0021] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0022] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0023] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order; for example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0024] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0025] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0026] The first aspect of this application provides a composite cathode, comprising: a cathode material layer; and a protective layer disposed on the surface of the cathode material layer, the protective layer comprising an additive capable of forming a CEI film on the surface of the cathode material layer under predetermined formation conditions; wherein the additive is a lithium salt.
[0027] By setting a protective layer on the surface of the positive electrode material layer, and forming a CEI film on the surface of the positive electrode material layer under preset formation conditions through additives in the protective layer, the protective layer and the CEI film provide dual protection for the positive electrode material layer, preventing contact between the electrolyte and the positive electrode material layer, reducing the dissolution of transition metals, and eliminating the need to consider the solubility between the electrolyte and the additives, the cycle performance of the composite positive electrode is effectively improved, thereby improving the cycle performance of the battery.
[0028] Optionally, the preset formation conditions include a formation voltage U satisfying: U≥4.2V. This voltage range allows additives in different composite cathodes to form a CEI film, improving the applicability and stability of the composite cathode. Alternatively, the formation voltage U satisfies: U≥4.6V, making the additives suitable for high-voltage cathode material layers.
[0029] Optionally, the lithium salt includes one or more of lithium difluorooxalate phosphate, lithium carbonate, lithium fluoride, lithium difluorooxalate borate, lithium perchlorate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(oxalate borate), lithium bis(oxalate borate), lithium bis(fluorosulfonyl)imide, lithium hexafluoroarsenate, lithium difluorophosphate, lithium difluorodioxalate phosphate, lithium (fluorosulfonyl)(perfluorobutylsulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide, lithium bis(fluoromalonic acid)borate, lithium bis(2-methyl-2-fluoromalonic acid)borate, and lithium 4,5-dicyano-2-trifluoromethyl-imidazolium.
[0030] Further, the additive has a mass fraction of 1%-45% in the protective layer, including but not limited to 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, and 45%. The additive within this mass fraction range stably decomposes under predetermined formation conditions to form a CEI film located on the side of the protective layer facing the electrolyte. Preferably, the additive accounts for 10%-40% of the mass fraction of the protective layer. More preferably, the additive accounts for 20%-30% of the mass fraction of the protective layer.
[0031] It is understandable that, due to the limited solubility of lithium salts in the electrolyte, even if some lithium salts in the protective layer dissolve in the electrolyte, it will not affect the technical effect of its decomposition on the positive electrode side to form a CEI film.
[0032] Furthermore, the thickness of the protective layer is 0.1 μm-25 μm, including but not limited to 0.1 μm, 0.2 μm, 0.5 μm, 1 μm, 3 μm, 5 μm, 10 μm, 15 μm, 20 μm, and 25 μm. This thickness range ensures normal ion transport while protecting the cathode material layer. Preferably, the thickness of the protective layer is 1 μm-20 μm.
[0033] In some embodiments, the protective layer further includes a solid electrolyte and a binder. The solid electrolyte and binder can form a framework for the decomposition of additives and provide a location for the formation of the CEI film, so that the CEI film formed by the decomposition of additives is formed on the side of the protective layer facing the electrolyte. The CEI film and the protective layer work together to protect the positive electrode material layer, prevent the electrolyte and the positive electrode material layer from contacting each other, and prevent the continuous formation of the CEI film, thereby causing lithium ion loss and a decrease in battery capacity.
[0034] This application does not specifically limit the materials of the solid electrolyte. Any known oxide solid electrolyte or polymer solid electrolyte can be used in this application without departing from the inventive concept. These are merely illustrative examples and not intended to limit the scope of protection. Optionally, the solid electrolyte includes at least one of oxide solid electrolytes and polymer solid electrolytes.
[0035] In some embodiments, the solid electrolyte is an oxide solid electrolyte. Specifically, the oxide solid electrolyte includes any one or more of garnet ceramics, LISICON-type oxides, NASICON-type oxides, or perovskite ceramics. For example, it can be Li... 6.5 La3Zr 1.75 Te 0.25 O 12 Li7La3Zr2O 12 Li 6.2 Ga 0.3 La 2.95Rb 0.05 Zr2O 12 , Li 6.85 La 2.9 Ca 0.1 Zr 1.75 Nb 0.25 O 12 , Li 6.25 Al 0.25 La3Zr2O 12 , Li 6.75 La3Zr 1.75 Nb 0.25 O 12 , Li 6.75 La3Zr 1.75 Nb 0.25 O 12 one or more of the above.
[0036] Wherein, the LISICON-type oxide includes Li 14 Zn(GeO4)4, Li 3+x (P 1-x Si x )O4 (where 0<x<1), Li 3+ x Ge x V 1-x O4 (where 0<x<1), one or more thereof.
[0037] Wherein, the chemical formula of the NASICON-type oxide is LiMM'(PO4)3, where M and M' are independently selected from Al, Ge, Ti, Sn, Hf, Zr or La. For example, it may be Li 1+x Al x Ge 2-x (PO4)3 (LAGP) (where 0≤x≤2), Li 1.3 Al 0.3 Ti 1.7 (PO4)3, Li 1+x Al x Ti 2-x (PO4)3 (LATP) (where 0≤x≤2), Li 1+x Y x Zr 2-x (PO4)3 (LYZP) (where 0≤x≤2), one or more of LiTi2(PO4)3, LiGeTi(PO4)3, LiGe2(PO4)3, and LiHf2(PO4)3.
[0038] Wherein, the perovskite-type ceramic includes Li 3.3 La 0.53 TiO3, LiSr 1.65Zr 1.3 Ta 1.7 O9, Li 2x-y Sr 1-x Ta y Zr 1-y O3 (where x=0.75y and 0.60<y<0.75), Li 3 / 8 Sr 7 / 16 Nb 3 / 4 Zr 1 / 4 O3, Li 3x La (2 / 3-x) TiO3 (where 0<x<0.25), one or more thereof.
[0039] Further, the ionic conductivity λ of the oxide solid electrolyte is 10 -5 S / cm≤λ≤10 -1 S / cm, including but not limited to 10 -5 S / cm, 2×10 -5 S / cm, 5×10 -5 S / cm, 10 -4 S / cm, 10 -3 S / cm, 10 -2 S / cm, 10 -1 S / cm.
[0040] In some embodiments, the solid electrolyte is a polymer solid electrolyte. Specifically, the polymer solid electrolyte includes one or more of polyethylene glycol, polyethylene oxide (PEO), poly(phenylene oxide) (PPO), poly(methyl methacrylate) (PMMA), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polyacrylic acid (PAA), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), and polyvinyl chloride (PVC).
[0041] Further, the ionic conductivity of the polymer solid electrolyte is >10 -4 S / cm.
[0042] In some embodiments, the mass fraction of the binder in the protective layer is 1% to 30%, including but not limited to 1%, 2%, 3%, 5%, 10%, 15%, 20%, 25%, 30%. Preferably, the mass fraction of the binder in the protective layer is 5% to 20%.
[0043] In this application, no particular limitation is made on the type of adhesive. Any known adhesive can be used in this application without departing from the inventive concept. These are merely illustrative examples and not intended to limit the scope of protection. Adhesives include, but are not limited to, one or more of the following: polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyvinylidene fluoride hexafluoropropylene (PVDF-HFP), polypropylene (PP), polyethylene (PE), styrene-butadiene rubber (SBR), nitrile rubber (NBR), sodium carboxymethyl cellulose (CMC), polyacrylic acid compounds, polyacrylonitrile, and sodium alginate.
[0044] In some embodiments, the protective layer also includes oxides to increase the inorganic loading of the protective layer, reduce the acidity of the electrolyte, and improve the compatibility of the electrolyte, including but not limited to magnesium oxide, calcium oxide, silicon oxide, aluminum oxide, hydrated aluminum oxide, sodium oxide, cobalt oxide, yttrium oxide, lanthanum oxide, titanium oxide, zinc oxide, and manganese oxide.
[0045] In some embodiments, the protective layer further includes a fast ion conductor. Further, the fast ion conductor includes, but is not limited to, one or more of lithium lanthanum zirconium tantalum oxide (LLZTO), lithium lanthanum zirconium oxide (LLZO), and lithium lanthanum titanium oxide (LLTO).
[0046] This application improves lithium-ion transport efficiency by adding fast ion conductors to the protective layer, thereby increasing the ion conductivity within the protective layer, avoiding the increase in internal resistance of the battery caused by the protective layer, and improving the battery's capacity performance.
[0047] In some embodiments, the cathode material layer includes an active material, which is a compound capable of reversibly inserting and deintercalating lithium. Specifically, it may include lithium transition metal composite oxides, lithium-containing metal compounds, elemental sulfur, and their compounds.
[0048] Optionally, the active material may be a high-potential active material. High-potential active materials offer advantages such as high capacity, high voltage plateau, good cycle stability, low self-discharge rate, and tunable ion diffusion performance, resulting in higher energy density in the battery. This helps improve the battery's energy output efficiency and power density, and extends its lifespan and cycle life. Specifically, the active material includes at least one of nickel, manganese, and cobalt.
[0049] In some embodiments, the active material is a ternary material, specifically including the three metal elements nickel, cobalt, and manganese. For example, the active material includes, but is not limited to, one or more of NCM811, NCM622, and NCM523.
[0050] In some embodiments, the active material is a manganese-rich material. Exemplarily, the positive electrode active material includes manganese-rich layered oxides, Li... 0.7 Mn0.78 Co 0.22 O2 (LMCO), Li 0.75 Mn 0.78 Co 0.11 Ni 0.11 O2 (LMCNO), Li 0.74 Mn 0.78 Ni 0.22 One or more of O2 (LMNO).
[0051] In some embodiments, the active material is a lithium-rich manganese-based material. For example, the positive electrode active material is xLi2MnO3·(1-x)LiMO2, where M is one or more of the transition metals Ni, Mn, and Co, and the value of x is in the range of 0 < x < 1.
[0052] In some embodiments, the positive electrode active material layer also includes a conductive agent.
[0053] In some embodiments, the conductive agent includes, but is not limited to, one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, carbon nanofibers, and graphene.
[0054] A second aspect of this application provides a method for preparing the composite positive electrode in the above embodiments, characterized by comprising the following steps:
[0055] S1, mix the additives and solvents to form a protective layer precursor;
[0056] S2, the protective layer precursor is coated on the surface of the cathode material layer to form the first intermediate product;
[0057] S3, bake the first intermediate product to obtain the second intermediate product;
[0058] S4, the second intermediate product is pressed to obtain a composite cathode.
[0059] By coating a protective layer precursor onto a cathode material layer, followed by baking and pressing of the protective layer precursor and the cathode material layer, a composite cathode with a protective layer is obtained. This preparation method helps to improve the bonding strength between the protective layer and the cathode material layer, thereby ensuring the strength of the composite cathode and effectively enhancing the stability of the CEI film formed by the additives.
[0060] It should be noted that the thickness of the protective layer mentioned in this application refers to the thickness of the protective layer precursor after baking and pressing.
[0061] In some embodiments, the protective layer further includes a solid electrolyte and a binder. Therefore, in step S1, the solid electrolyte powder, binder, additives, and solvent are mixed to form the protective layer. The solid electrolyte powder, binder, and additives are dispersed using a solvent to ensure the uniformity of the protective layer. Optionally, the solvent includes, but is not limited to, one or more of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), ethanol, and acetone.
[0062] Optionally, in step S3, the baking temperature of the first intermediate product is 60℃-150℃, including but not limited to 60℃, 70℃, 80℃, 90℃, 100℃, 110℃, 120℃, 130℃, 140℃, and 150℃.
[0063] Baking time is 0.5min-30min, including but not limited to 0.5min, 1min, 2min, 3min, 5min, 8min, 10min, 15min, 20min, 25min, and 30min.
[0064] Optionally, in step S4, the pressing pressure of the second intermediate product is 0.5t-20t, including but not limited to 0.5t, 1t, 2t, 3t, 5t, 8t, 10t, 15t, and 20t.
[0065] A third aspect of this application provides a lithium-ion battery, which includes a composite positive electrode, a negative electrode, and a separator as described above.
[0066] In some embodiments, the diaphragm may be formed of a microporous insulating material, wherein a non-aqueous liquid may wet the pore structure of the diaphragm.
[0067] In some embodiments, the negative electrode includes a negative electrode active material layer. In this application, there are no particular limitations on the negative electrode active material; any material capable of electrochemically adsorbing and releasing lithium ions is acceptable. Exemplarily, the negative electrode active material can be selected from carbonaceous materials, metal compound materials, or their oxides, carbides, nitrides, silicides, sulfides, phosphides, etc. These materials can be used alone or in combination of two or more.
[0068] In some embodiments, carbon materials can be selected as the negative electrode active material. Specifically, one or more of the following can be selected: graphite, needle coke, amorphous carbon, carbon-containing mesophase, carbon fiber, and carbon materials with low graphitization. Graphite can include natural graphite, artificial graphite, etc. Alternatively, materials obtained by coating these materials with carbon materials, such as amorphous carbon or graphitized compounds, can also be used. Examples of amorphous carbon include particles obtained by sintering a monolithic mesophase and particles obtained by sintering a carbon precursor after infusible treatment. Examples of carbonaceous particles with low graphitization include particles obtained by sintering organic matter at temperatures typically below 2500°C.
[0069] In addition, non-metallic materials that can be used as negative electrode active materials include elemental silicon and its compounds, such as Si and SiOx (0≤x<2). Since silicon-containing materials are prone to expansion and easy to fall off from the negative electrode current collector, and have poor conductivity, they are often used in combination with carbon materials, such as core-shell structures containing carbon coating layers.
[0070] In some embodiments, elemental metals and metal compounds can be selected as negative electrode active materials, for example, compounds containing metals or metalloids such as Li, Ag, Al, Bi, Cu, Ga, Ge, In, Ni, Pb, Sb, Si, Sn, Sr, and Zn.
[0071] In some embodiments, the negative electrode is also provided with the above-mentioned protective layer, which includes additives that can form an SEI film on the negative electrode active material layer under preset formation conditions to improve the cycle performance of the negative electrode.
[0072] The present application will be further described below with reference to specific embodiments and comparative examples.
[0073] Example 1
[0074] The first aspect of this embodiment provides a composite positive electrode, including a positive electrode material layer and a protective layer disposed on the side of the positive electrode material layer facing the electrolyte. The positive electrode material layer includes an active material NCM811, and the protective layer includes an additive lithium fluoride. The mass fraction of the additive in the protective layer is 30%, and the thickness of the protective layer is 15 μm.
[0075] The second aspect of this embodiment provides a method for preparing the composite cathode, comprising the following steps: S1, dispersing the additive lithium fluoride, the solid electrolyte lithium lanthanum zirconium oxide, and the binder PVDF in a mass ratio of 30:50:20 in the solvent NMP, and mixing them to form a protective layer precursor; S2, coating the protective layer precursor onto the surface of the cathode material layer to form a first intermediate product; S3, baking the first intermediate product at 90 °C for 15 min to obtain a second intermediate product; S4, pressing the second intermediate product under a pressing pressure of 10 t to obtain the composite cathode.
[0076] This embodiment provides a lithium-ion battery, comprising a composite positive electrode, a negative electrode, and a separator. The positive electrode active material is NCM811, and the negative electrode active material is graphite. After the lithium-ion battery is prepared, it undergoes formation, is charged to 4.3V at 0.1C, and then allowed to stand for 5 minutes.
[0077] Example 2
[0078] The first aspect of this embodiment provides a composite positive electrode, including a positive electrode material layer and a protective layer disposed on the side of the positive electrode material layer facing the electrolyte. The positive electrode material layer includes an active material NCM811, and the protective layer includes an additive lithium perchlorate. The mass fraction of the additive in the protective layer is 30%, and the thickness of the protective layer is 15 μm.
[0079] The second aspect of this embodiment provides a method for preparing the composite cathode, comprising the following steps: S1, dispersing additives perchloric acid, solid electrolyte lithium lanthanum zirconium oxide, and binder PVDF in a mass ratio of 30:50:20 in solvent NMP, and mixing to form a protective layer precursor; S2, coating the protective layer precursor onto the surface of the cathode material layer to form a first intermediate product; S3, baking the first intermediate product at 90 °C for 15 min to obtain a second intermediate product; S4, pressing the second intermediate product under a pressing pressure of 10 t to obtain the composite cathode.
[0080] This embodiment provides a lithium-ion battery, comprising a composite positive electrode, a negative electrode, and a separator. The positive electrode active material is NCM811, and the negative electrode active material is graphite. After the lithium-ion battery is prepared, it undergoes formation, is charged to 4.3V at 0.1C, and then allowed to stand for 5 minutes.
[0081] Example 3
[0082] The first aspect of this embodiment provides a composite positive electrode, including a positive electrode material layer and a protective layer disposed on the side of the positive electrode material layer facing the electrolyte. The positive electrode material layer includes an active material NCM811, and the protective layer includes an additive lithium tetrafluoroborate. The mass fraction of the additive in the protective layer is 30%, and the thickness of the protective layer is 15 μm.
[0083] The second aspect of this embodiment provides a method for preparing the composite cathode, comprising the following steps: S1, dispersing the additive lithium tetrafluoroborate, the solid electrolyte lithium lanthanum zirconium oxide, and the binder PVDF in a mass ratio of 30:50:20 in the solvent NMP, and mixing them to form a protective layer precursor; S2, coating the protective layer precursor onto the surface of the cathode material layer to form a first intermediate product; S3, baking the first intermediate product at 90 °C for 15 min to obtain a second intermediate product; S4, pressing the second intermediate product under a pressing pressure of 10 t to obtain the composite cathode.
[0084] This embodiment provides a lithium-ion battery, comprising a composite positive electrode, a negative electrode, and a separator. The negative electrode active material is graphite. After the lithium-ion battery is prepared, it undergoes formation, is charged to 4.3V at 0.1C, and then allowed to stand for 5 minutes.
[0085] Example 4
[0086] The first aspect of this embodiment provides a composite positive electrode, including a positive electrode material layer and a protective layer disposed on the side of the positive electrode material layer facing the electrolyte. The positive electrode material layer includes an active material NCM811, and the protective layer includes an additive lithium difluorooxalate borate. The mass fraction of the additive in the protective layer is 30%, and the thickness of the protective layer is 15 μm.
[0087] The second aspect of this embodiment provides a method for preparing the composite cathode, comprising the following steps: S1, dispersing the additive lithium difluorooxalate borate, the solid electrolyte lithium lanthanum zirconium oxide, and the binder PVDF in a mass ratio of 30:50:20 in the solvent NMP, and mixing them to form a protective layer precursor; S2, coating the protective layer precursor onto the surface of the cathode material layer to form a first intermediate product; S3, baking the first intermediate product at 120 °C for 10 min to obtain a second intermediate product; S4, pressing the second intermediate product under a pressing pressure of 10 t to obtain the composite cathode.
[0088] This embodiment provides a lithium-ion battery, comprising a composite positive electrode, a negative electrode, and a separator. The negative electrode active material is graphite. After the lithium-ion battery is prepared, it undergoes formation, is charged to 4.3V at 0.1C, and then allowed to stand for 5 minutes.
[0089] Example 5
[0090] The first aspect of this embodiment provides a composite positive electrode, including a positive electrode material layer and a protective layer disposed on the side of the positive electrode material layer facing the electrolyte. The positive electrode material layer includes an active material NCM811, and the protective layer includes an additive lithium fluoride. The mass fraction of the additive in the protective layer is 45%, and the thickness of the protective layer is 20 μm.
[0091] The second aspect of this embodiment provides a method for preparing the composite cathode, comprising the following steps: S1, dispersing the additive lithium fluoride, the solid electrolyte lithium lanthanum zirconium oxide, and the binder PVDF in a mass ratio of 45:40:15 in the solvent NMP, and mixing them to form a protective layer precursor; S2, coating the protective layer precursor onto the surface of the cathode material layer to form a first intermediate product; S3, baking the first intermediate product at 90°C for 15 min to obtain a second intermediate product; S4, pressing the second intermediate product under a pressing pressure of 10 t to obtain the composite cathode.
[0092] This embodiment provides a lithium-ion battery, comprising a composite positive electrode, a negative electrode, and a separator. The positive electrode active material is NCM811, and the negative electrode active material is graphite. After the lithium-ion battery is prepared, it undergoes formation, is charged to 4.3V at 0.1C, and then allowed to stand for 5 minutes.
[0093] Example 6
[0094] The first aspect of this embodiment provides a composite positive electrode, including a positive electrode material layer and a protective layer disposed on the side of the positive electrode material layer facing the electrolyte. The positive electrode material layer includes an active material NCM811, and the protective layer includes an additive lithium fluoride. The mass fraction of the additive in the protective layer is 1%, and the thickness of the protective layer is 5 μm.
[0095] The second aspect of this embodiment provides a method for preparing the composite cathode, comprising the following steps: S1, dispersing the additive lithium fluoride, the solid electrolyte lithium lanthanum zirconium oxide, and the binder PVDF in a mass ratio of 1:69:30 in the solvent NMP, and mixing them to form a protective layer precursor; S2, coating the protective layer precursor onto the surface of the cathode material layer to form a first intermediate product; S3, baking the first intermediate product at 90 °C for 15 min to obtain a second intermediate product; S4, pressing the second intermediate product under a pressing pressure of 10 t to obtain the composite cathode.
[0096] This embodiment provides a lithium-ion battery, comprising a composite positive electrode, a negative electrode, and a separator. The positive electrode active material is NCM811, and the negative electrode active material is graphite. After the lithium-ion battery is prepared, it undergoes formation, is charged to 4.3V at 0.1C, and then allowed to stand for 5 minutes.
[0097] Example 7
[0098] The difference between Example 7 and Example 1 is that the protective layer in Example 7 was not pressed during preparation, but the rest are the same.
[0099] The first aspect of this embodiment provides a composite positive electrode, including a positive electrode material layer and a protective layer disposed on the side of the positive electrode material layer facing the electrolyte. The positive electrode material layer includes an active material NCM811, and the protective layer includes an additive lithium fluoride. The mass fraction of the additive in the protective layer is 30%, and the thickness of the protective layer is 15 μm.
[0100] The second aspect of this embodiment provides a method for preparing the composite cathode, comprising the following steps: S1, dispersing the additive lithium fluoride, the solid electrolyte lithium lanthanum zirconium oxide, and the binder PVDF in a mass ratio of 30:50:20 in the solvent NMP, and mixing them to form a protective layer precursor; S2, coating the protective layer precursor onto the surface of the cathode material layer to form a first intermediate product; S3, baking the first intermediate product at 90 °C for 15 min to obtain the composite cathode.
[0101] This embodiment provides a lithium-ion battery, comprising a composite positive electrode, a negative electrode, and a separator. The positive electrode active material is NCM811, and the negative electrode active material is graphite. After the lithium-ion battery is prepared, it undergoes formation, is charged to 4.3V at 0.1C, and then allowed to stand for 5 minutes.
[0102] Comparative Example 1
[0103] The only difference between Comparative Example 1 and Example 1 is that the composite positive electrode of Comparative Example 1 has no protective layer and the additives are dissolved in the electrolyte.
[0104] The first aspect of this comparative example provides a positive electrode, including a positive electrode material layer, the positive electrode material layer including the active material NCM811.
[0105] The second aspect of this comparative example provides a lithium-ion battery, which includes a composite positive electrode, a negative electrode, a separator, and an electrolyte. The negative electrode active material is graphite, and the electrolyte includes the additive lithium fluoride. After the lithium-ion battery is prepared, it undergoes formation, is charged to 4.3V at 0.1C, and then allowed to stand for 5 minutes.
[0106] Comparative Example 2
[0107] The only difference between Comparative Example 2 and Example 1 is that the protective layer of the composite positive electrode in Comparative Example 2 does not contain any additives; all other aspects are the same.
[0108] The first aspect of this comparative example provides a positive electrode, including a positive electrode material layer, the positive electrode material layer including an active material NCM811.
[0109] The second aspect of this comparative example provides a lithium-ion battery, which includes a positive electrode, a negative electrode, and a separator. Graphite is selected as the active material for the negative electrode. After the lithium-ion battery is prepared, it undergoes formation, is charged to 4.3V at 0.1C, and then allowed to stand for 5 minutes.
[0110] Test case
[0111] (1) ICP test (determination of Mn on the negative electrode side) 2+ (ion content)
[0112] A: Weigh approximately 1 g of negative electrode powder (accurate to ±0.0003 g) from each example and comparative example, place them in a 100 ml beaker, add a small amount of distilled water to moisten the bottom of the beaker, then add 5 ml of 12 mol / L aqua regia to dissolve it, heat on an electric heating plate for 20 min, remove and cool, dilute and then test. Introduce the prepared series of standard solutions into an iCAP7000 inductively coupled plasma optical transilluminator (ICP). Measure the intensity of manganese in the standard solution at the wavelength of the target element, manganese. When the linear correlation coefficient r of the working curve is ≥0.9995, the measurement can be performed. The test results are shown in Table 1.
[0113] (2) Capacity test
[0114] At room temperature, the cells were charged at a constant current of 1C to 4.3V, then charged at a constant voltage of 4.3V until the current decreased to 0.002A. After resting for ten minutes, the cells were discharged at 0.1C to 3V. This charge-discharge cycle was repeated three times, and the average discharge capacity of the three cycles was taken as the actual capacity of a single cell. Five cells were tested, and the average capacity of the five cells was taken. The test results are shown in Table 1.
[0115] (3) Cyclic life test
[0116] Batteries from each embodiment and comparative example were cycled for 200 cycles at room temperature under 0.1C / 0.1C charge / discharge conditions, and the average value of the ratio of the discharge capacity of the two batteries in the 200th cycle to the discharge capacity in the 1st cycle was calculated.
[0117]
[0118] As can be seen from the above experimental data, compared with Example 1 and Example 7, the protective layer and the positive electrode material layer have improved bonding strength after pressing, which better prevents the electrolyte and the positive electrode material layer from contacting each other, thereby improving the battery capacity and battery cycle performance, and reducing the content of transition metal ions on the negative electrode side.
[0119] Compared with Comparative Example 1, the method of placing the additive in the protective layer can better protect the positive electrode material layer than dissolving the additive in the electrolyte, preventing the electrolyte from contacting the positive electrode material layer, effectively improving the battery cycle performance, and significantly reducing the content of transition metal ions on the negative electrode side.
[0120] Compared with Comparative Example 1 and Comparative Example 2, compared with the method of only setting a protective layer, the presence of additives can further protect the positive electrode material layer, further prevent the contact between the electrolyte and the positive electrode material layer, improve the battery capacity and battery cycle performance, and effectively reduce the content of transition metal ions on the negative electrode side.
[0121] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0122] The above embodiments merely illustrate several implementation methods of this application, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the patent application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this patent application should be determined by the appended claims.
Claims
1. A composite positive electrode, characterized in that, include: A positive electrode material layer, wherein the positive electrode material layer includes an active material, wherein the active material includes at least one of nickel, manganese, and cobalt. and A protective layer is disposed on the surface of the positive electrode material layer. The protective layer includes an additive, a solid electrolyte, and a binder. The additive is capable of forming a CEI film on the surface of the positive electrode material layer under preset formation conditions. The solid electrolyte and the binder are capable of forming a framework for the decomposition of the additive and providing a location for the formation of the CEI film. The additive is a lithium salt; The preset formation conditions include a formation voltage U that satisfies U≥4.2V.
2. The composite positive electrode according to claim 1, characterized in that, The lithium salts include one or more of lithium difluorooxalate phosphate, lithium carbonate, lithium fluoride, lithium difluorooxalate borate, lithium perchlorate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(oxalate borate), lithium bis(oxalate borate), lithium bis(fluorosulfonyl)imide, lithium hexafluoroarsenate, lithium difluorophosphate, lithium difluorodioxalate phosphate, lithium (fluorosulfonyl)(perfluorobutylsulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imino, lithium bis(fluoromalonic acid)borate, lithium bis(2-methyl-2-fluoromalonic acid)borate, and 4,5-dicyano-2-trifluoromethyl-imidazolium lithium.
3. The composite positive electrode according to claim 1, characterized in that, The additive has a mass fraction of 1%-45% in the protective layer.
4. The composite positive electrode according to claim 1, characterized in that, The thickness of the protective layer is 0.1μm-25μm.
5. The composite positive electrode according to claim 1, characterized in that, The solid electrolyte includes at least one of oxide solid electrolyte and polymer solid electrolyte.
6. A method for preparing a composite positive electrode as described in any one of claims 1-5, characterized in that, Includes the following steps: Additives, solid electrolytes, binders and solvents are mixed to form a protective layer precursor; The protective layer precursor is coated onto the surface of the cathode material layer to form a first intermediate product; The first intermediate product is baked to obtain the second intermediate product; The second intermediate product was pressed to obtain a composite cathode; The additive is a lithium salt; The positive electrode material layer includes an active material, which includes at least one of nickel, manganese, and cobalt. The additive can form a CEI film on the surface of the positive electrode material layer under preset formation conditions, and the solid electrolyte and the binder can form a framework for the decomposition of the additive and provide the formation location of the CEI film. The preset formation conditions include a formation voltage U that satisfies U≥4.2V.
7. A lithium-ion battery, characterized in that, The lithium-ion battery includes a composite positive electrode, a negative electrode, and a separator as described in any one of claims 1-5.
Citation Information
Patent Citations
Lithium ion battery and positive pole piece thereof
CN115602786A
Nonaqueous electrolyte, secondary battery, and electric device
CN116918122A